Interação mãe-criança autista em situações de brincadeira livre e computador - Coutinho, Ana Flavia de Oliveira Borba (2012)
Abstract. Autism is classified as a Pervasive Developmental Disorder (PDD) characterized by a triad of impairment involving losses in the development of social interaction, communication and imagination. Its etiology is diverse, with varying degrees of impairment, such factors make that the promotion of social interaction of autistic children represents a major challenge. With technological advances, the computer has become as an auxiliary tool in the interactive process, justifying the development of studies that focus on social interaction of autistic children in digital environments. This study aimed to analyze the mother-child autistic interaction in situations of free play and a situation involving the use of a computer. The specific objectives aimed to apprehend maternal conceptions about autism; to identify and compare the communication styles of mother-child autistic in situations of free play and using a computer; and also analyze the strategies used by mothers to stimulate the child's interest in the activities. This is a descriptive study, characterized by a qualitative and quantitative approach with the participation of four mother-child dyads, aged 4-6 years, and used the following instruments: Sociodemographic Questionnaire; Semi-structured interview; Filming in free play and using a computer; and Childhood Autism Rating Scale (CARS). The participants belong to the Autism Parents and Friends Association (ASAS) in Joao Pessoa and the data were collected at their homes. Four film sessions were conducted with each dyad (two in free play and two using a computer), each one with a total duration of 20 minutes, considering the central 10 minutes. The systematic observations of the sessions in conjunction with the semi-structured interviews enabled the development of software for each child that was used in the third and fourth session. For the processing and analyses of the contents brought out from the interviews was used the model of Content Analysis proposed by Bardin. The recordings were transcribed under the rules of Codes for Human Analysis of Transcripts (CHAT) which consists of a transcription system of Child Language Data Exchange System (CHILDES). It was used categories and subcategories related to maternal communicative styles and communicative behaviours of the child. Among them it was identified continuity, discontinuity and frequency of interactive episodes, considering their co-occurrence and duration. In the analysis of interactions observations among dyads, there were a variety of continuous and discontinuous episodes permeated by maternal strategies to promote child development. The challenge was characterized by the role of the mediator who has to work constantly to stimulate the child to focus to achieve the goal of the program and to be able to perceive the mediator as an intentional agent performing the achievement of triad interaction proposed in this study: mother-child-computer.